Antibiotic resistance and serotype distribution of Shigella strains in Bangladesh over the period of 2014–2022: evidence from a nationwide hospital-based surveillance for cholera and other diarrheal diseases - Mokibul Hassan Afrad; Md. Taufiqul Islam; Yasmin Ara Begum; Md. Saifullah; Faisal Ahmmed; Zahid Hasan Khan; Zakir Hossain Habib; Ahmed Nawsher Alam; Tahmina Shirin; Taufiqur Rahman Bhuiyan; Edward T. Ryan; Ashraful Islam Khan; et al. (Microbiology Spectrum)
ABSTRACT The objective of this study was to assess the prevalence, antimicrobial resistance patterns, and risk factors linked to Shigella infections through a nationwide hospital-based diarrheal disease surveillance in Bangladesh. From May 2014 to May 2022, from a systematic sentinel surveillance of Shigella infections in over 10 hospitals across Bangladesh, stool specimens were collected from patients with acute watery diarrhea and tested for Shigella species by microbiological culture. The susceptibility to antibiotics was tested using the disk diffusion method. Structured questionnaires were used to collect participants’ socioeconomic status and clinical, sanitation, and food history. Out of 24,357 stool specimens, 1.8% were positive for Shigella species, with a higher prevalence among males (58%). Children in the 6–17 age group were found to be at the highest risk of Shigella infections. The most prevalent serotype was Shigella flexneri (79.5%), followed by Shigella sonnei. S. flexneri serotype 2a was the most common (63.3%) among all Shigella serotypes. Antibiotic susceptibility testing showed over 99% of isolates resistant or with intermediate susceptibility to one of the seven antibiotics tested. About 96% of S. flexneri and all S. sonnei isolates demonstrated resistance to at least one quinolone class of antibiotics, particularly ciprofloxacin or nalidixic acid. S. sonnei showed higher antibiotic resistance and multidrug resistance compared to S. flexneri. The high level of resistance to ciprofloxacin highlights the need for more prudent use of this antibiotic and improved hygiene and sanitation. The study emphasized the importance of regular monitoring of drug resistance to effectively manage Shigella infections. These findings may provide the epidemiological evidence for conducting future appropriate Shigella vaccine clinical trials in Bangladesh.IMPORTANCEThis nationwide study in Bangladesh assessed Shigella infections from 2014 to 2022 from clinical samples. S. flexneri was predominant, with concerning antibiotic resistance, notably to ciprofloxacin and nalidixic acid in over 96% of isolates. This emphasizes the urgency of prudent antibiotic use and improved hygiene. The findings provide crucial antimicrobial resistance patterns of Shigella species, highlighting the need for ongoing resistance monitoring and potentially informing future vaccine trials.